Anesthesia Management and Intensive Care in Cesarean Section on a Woman with Placenta Accreta with Placenta Accreta Index (PAI) Score of ≥ 6: A Case Report - Prasetyo, Denny; Isngadi, Isngadi (Journal of Anaesthesia and Pain, 2025)
Background: Placenta accreta spectrum (PAS) is the leading cause of peripartum hysterectomy. PAS often results in massive postpartum haemorrhage, requiring careful perioperative planning and multidisciplinary coordination. This case report aims to discuss the anesthesia management and intensive care provided to a patient who underwent cesarean section (CS) with a placenta accreta index (PAI) score of ≥6.Case: This case involves a 32-year-old multipara with a history of three previous CS. The patient was scheduled for CS due to breech presentation and suspected total placenta previa/accreta with a PAI score of ≥ 6. A combined spinal-epidural (CSE) was chosen as anesthesia management. During surgery, the patient experienced severe bleeding (3,000 mL) with hypotension (blood pressure 81/44 mmHg) and bradycardia (heart rate 60 beats per minute). Central iliac artery balloon occlusion (CIABO) was performed by a radiologist for temporary blood flow occlusion. Resuscitation included 3,000 mL crystalloids, 1,000 mL colloids, and 1,200 mL blood product. A baby girl was delivered (Apgar 7–9). The patient remained stable in the intensive care unit and was transferred to the regular ward the following day.Conclusion: Comprehensive perioperative planning and multidisciplinary coordination in managing PAS are important. Despite severe intraoperative hemorrhage and hemodynamic instability, the use of combined spinal-epidural anesthesia, prompt fluid and blood resuscitation, and intensive monitoring ensured a favorable outcome. Postoperative lactate value and early transfer from the ICU to the regular ward indicate successful management.